Utilization of Palmitic Acid by Mycobacterium avium - McCarthy, Charlotte (1971)
Mycobacterium avium accumulates (14)C-palmitic acid with saturation kinetics; the process is both temperature dependent and pH sensitive. The fatty acid is incorporated into triglyceride in vivo and the conversion is detectable within 5 min after exposure of the cells to (14)C-palmitic acid. The triglyceride is rapidly utilized because (14)CO(2) evolution from it begins within 30 min after (14)C-palmitic acid accumulation. Data from silicic acid column chromatography of extracts of cultures that have divided many times in medium containing (14)C-palmitic acid indicate that a large proportion of the cell lipid is triglyceride, but the radioactivity is widely dispersed among the other lipids. It is estimated that about 5% of the cell dry weight is triglyceride in a postexponential culture.